Adaptive frequency compensation for maximum and constant bandwidth feedback amplifiers. (21st December 2011) - Pennisi, Salvatore; Scotti, Giuseppe; Trifiletti, Alessandro
ABSTRACT We present an adaptive frequency compensation technique providing maximum bandwidth closed‐loop amplifiers. The approach exploits an auxiliary variable gain amplifier to implement an electrically tunable compensation capacitor proportional to the feedback factor. In this manner, the closed‐loop bandwidth is kept ideally constant irrespective of the closed‐loop gain. The proposed method can be applied to any amplifier adopting dominant‐pole compensation. As an example, we designed a CMOS amplifier providing 66‐dB direct current gain and 310‐MHz gain‐bandwidth product. For closed‐loop gains ranging from 1 to 10, the closed‐loop bandwidth was found never lower than 401 MHz (noinverting configuration) and 229 MHz (inverting configuration). A similar amplifier with equal gain‐bandwidth product, but adopting the traditional fixed compensation approach, would exhibit a closed‐loop bandwidth reduced to 33 MHz (noninverting) and 30 MHz (inverting) when the gain magnitude is set to 10. The enhanced frequency performance is obtained with a 48% increase in current consumption, whereas the other main operational amplifier performance parameters remain almost unchanged compared with the standard solution. Copyright © 2011 John Wiley & Sons, Ltd.